ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN - Niken Widyastuti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
Basic mission of a business today is no longer a profit but value creation and value addition for customer. The survey was conducted in the reseach process to determine the level of customer satisfaction on service quality dimensions of Harris & Pop Hotels Denpasar. This research is based on five variables, Reliability (ability of the company to provide prompt service and reliable), Responsiveness (response-ability or alertness companies to help customers and provide fast service), Assurance (ability, courtesy, and trustworthiness which is owned by the staff, danger free, risk, and doubt), Empathy (the ease of having good communications and able to understand customer needs), and Tangible (physical facilities, equipments, employee performance, and means of communications). The analysis is performed based on an approach of importance-performance analysis that show the dimensions of empathy and assurance are considered the most influence on the customers decision to use the services of Harris & Pop Hotels Denpasar.